Virtual learning environment and its relationship with worker characteristics and occupational accident rates - Hernández, Wilder Alfonso Duarte; Gómez, LydaCamila Gómez (Frontiers in Public Health, 2022)
Information and Communication Technologies (ICT) have been employed widely in Occupational Health and Safety Management Systems training programs. However, it is necessary to investigate the influence and workers characteristics to ensure effectiveness. The study presents the relationship between demographic characterization and learning styles with the satisfaction and approval of a training course for teachers through virtual modality and the incidence in accident indicators of an educational institution. Analytical and longitudinal study. In 2019, 385 teachers participated in a virtual course on falls prevention. Learning styles were surveyed and records of teachers' entrance and approval of the course were consolidated. The evaluation of the course by teachers was reviewed and the behavior of accident frequency and severity indicators were analyzed comparing 2018 and 2019. To determine significant relationships, Cramer's V was applied for learning styles and demographic characteristics with access and course approval. ANOVA was applied for the demographic variables and the evaluation given by teachers to the course. T-test was used to compare the average values of the indicators for the period 2018-2019. Statistical relationships were found between the predominant learning style and access (P <0,01) and approval (P <0,01). Educational level of the population with access (P <0,05) and course approval (P <0,01). In addition to the age range and the rating given to the methodology applied in the course (P <0,05). No differences were found between the values of the indicators. By identifying significant relationships between learning styles and demographic characteristics of the working population and the use of virtual learning environments, it is important to continue researching the influence of workers' characteristics and didactic methodologies for the design of virtual learning environments that encourage workers to follow safe procedures during their work.